URBAN AGRICULTURE COMMERCIALIZATION; AN ALTERNATIVE TO FOOD SECURITY (Case of Mekelle city) - Gebrekiros Hagos Belay; Abrha Gebreslassie; Amanuel Teklay; Mulugeta Tesfay (Socio-Economics/Agribusiness Department, 2020)
The study was commenced with the general objective of urban Agriculture commercialization specifically Dairy Product in Mekelle city, Tigrai Ethiopia .100 households were selected using simple random sampling method. Data were collected using formal survey which is questionnaire. The data collected were processed using both descriptive and two stage least square method/ Multiple regression econometric models specifically logit model. The binary Dairy Product model results revealed that Extent of education of the household head, family size, distance to the nearest market center, and total Dairy Product owned played significant role in commercialization decision. The second-step selection estimation indicated that Extent of education of the household head, visit by extension agents, total dairy products owned and owned land size significantly affected Extent of commercialization measures the fraction of sales to the total value of dairy products owned by the household. The researchers recommend that any stakeholder, institutions like agricultural institute , government with its extension workers and other development institutions and partners should give due emphasis on capacity building through formal and informal ways, which increases the owner of the Dairy Product a bargaining power in the market by getting information related price, demand and supply , production and management technologies Besides, facilitate Dairy Product market outlets near to them in the region and creating an interface with other regions, which minimize operation and increment efficiency. Finally, stakeholders should give emphasis to the major challenges of market infrastructure, shortage in pasture lands and disease for they could create a bottleneck effect in the remedy and food of the society positively and negatively measuring their implementation performance.